Dysregulation of autophagy during photoaging reduce oxidative stress and inflammatory damage caused by UV - Zhang, Zhongsong; Tan, Run; Xiong, Zuanyu; Feng, Yanyan; Chen, Long (Frontiers in Pharmacology, 2025)
Photoaging, the premature aging of skin due to chronic ultraviolet (UV) exposure, is a growing concern in dermatology and cosmetic science. While UV radiation is known to induce DNA damage, oxidative stress, and inflammation in skin cells, recent research unveils a promising countermeasure: autophagy. This review explores the intricate relationship between autophagy and photoaging, highlighting how this cellular recycling process can mitigate UV-induced damage. We begin by examining the differential impacts of UVA and UVB radiation on skin cells and the role of oxidative stress in accelerating photoaging. Next, we delve into the molecular mechanisms of autophagy, including its various forms and regulatory pathways. Central to this review is the discussion of autophagy’s protective functions, such as the clearance of damaged organelles and proteins, and its role in maintaining genomic integrity. Furthermore, we address the current challenges in harnessing autophagy for therapeutic purposes, including the need for selective autophagy inducers and a deeper understanding of its context-dependent effects. By synthesizing recent advancements and proposing future research directions, this review underscores the potential of autophagy modulation as a novel strategy to prevent and treat photoaging. This comprehensive analysis aims to inspire further investigation into autophagy-based interventions, offering new hope for preserving skin health in the face of environmental stressors.